Proposta de um modelo de Customer-Based Brand Equity (CBBE) para aplicação em Atrativos Turísticos: um estudo no Complexo Turístico Itaipu - Chibiaqui, Rodrigo (2019)
Despite the increasing importance of brand value in a wide range of segments, tourism attractions are usually analyzed under the image approach, disregarding other dimensions that comprise the Customer-Based Brand Equity (CBBE). As a scale for the measurement of tourist attractions CBBE was not available in the literature, this work proposed a specific scale for the Itaipu Tourist Complex (CTI), object of this study, based on the brands literature and on scales used in tourism destination studies. The theoretical model was empirically tested through a survey with 409 visitors. The validity of the scale and the proposed theoretical model were analyzed through descriptive statistics, exploratory factorial analysis, correlations, confirmatory factorial analysis and structural equations modeling. A cluster analysis was performed in order to detect differences between the groups that better and worse evaluate the CTI CBBE, as well as the impacts that different levels of loyalty can generate in the theoretical model. The main results of the study were the validation of the four dimensions of the CBBE proposed by Konecnik (2006); the reformulation of the observable variables that set each dimension; the observation of the correlations between dimensions, which suggests that brand image (IM) is the dimension with less correlation among the others, as well as that brand knowledge (CM) and perceived quality (QP) are the factors that most influence the CBBE; the observation of cause and effect relationships between dimensions, showing that QP positively affects IM and brand loyalty (LM). Finally, through the cluster analysis it was possible to show that travelers with a lot of travel experience, high level of education and income are the ones that worst evaluate the attraction’s brand equity, mainly in the loyalty and perceived quality dimensions, showing that this public is harder to enchant.